Contribution of organic amendments to soil properties and survival of Stenocarpella on corn stalk - Faria, Mírian Rabelo de (2016)
No-tillage systalks, especially in corn monoculture, contribute to the incidence of diseases caused by necrotrophic pathogens such as Stenocarpella spp. One strategy to reduce the survival of such a pathogen is through the application of organic matter and nutrients in the soil. The aim of this study was to evaluate the effect of the application of organic wastes and urea on the survival of Stenocarpella spp. in corn stalks. The assays were conducted in experimental area of Lavras and Corn Sete Lagoas. Corn stalks, previously infested with the pathogen, were laid on the floor in the field for a period of three months after application of the organic wastes (Poultry litter, swine manure, fish hydrolyzed, and sewage sludge), urea a negative control with untreated stalks and a positive one with buried stalks. The indirect microbial activity (β-glucosidase and hydrolysis of fluorescein diacetate (FDA) and urease), chemical soil analysis and dynamics of pathogen population, through qPCR, were evaluated at the end of the period. The calcium content increased with application of Poultry litter in both areas. Poultry litter and sewage sludge increased β-glucosidase activity and hydrolysis of FDA at both locations. The pathogen population dynamics, the buried stalkstalks reduced the pathogen at both locations, the second highest reduction was obtained by sewage sludge in Lavras and fish hydrolyzed and sewage sludge in Sete Lagoas. Therefore Fish hydrolyzed and sewage sludge were promising to induce suppressiveness, since increased the suppressivityrealted soil enzymatic activity and reduced the pathogen population.